Meta-Research in Biomedical Investigation: Gaps and Opportunities Based on Meta-Research Publications and Global Indicators in Health, Science, and Human Development - Ivan David Lozada-Martinez; David A. Hernandez-Paz; Ornella Fiorillo-Moreno; Yelson Alejandro Picón-Jaimes; Valmore Bermúdez (Publications)
Meta-research in biomedical science is crucial for ensuring rigour, relevance, and transparency in an era marked by the exponential growth of scientific publications. This study examines global and historical trends in meta-research activities within biomedicine and investigates their relationship with health, science, and human development indicators. A systematic analysis of 9633 publications from Scopus, Web of Science, and PubMed was conducted, focusing on publication volume, citation impact, and geographic distribution. Regression analyses reveal a significant positive association between meta-research activity and the Human Development Index (HDI), suggesting that meta-research contributes to societal advancement by enhancing evidence-based decision-making in health. However, no association was found between meta-research output and research and development (R&D) expenditure, reflecting the minimal resource requirements of secondary data-driven studies compared to primary or experimental research. Meta-research activity correlates positively with clinical trial completion, indicating its role in refining study designs and addressing evidence gaps. These findings highlight the importance of expanding meta-research in underrepresented regions to promote equity in scientific advancement and improve the reliability of biomedical knowledge. This result underscores the need for targeted support for meta-research, particularly in low- and middle-income countries with limited scientific infrastructure and resources for new knowledge generation.